2020
DOI: 10.1111/jonm.13168
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID‐19, psychological distress, work satisfaction and turnover intention among frontline nurses

Abstract: Aim To examine the relative influence of fear of COVID‐19 on nurses’ psychological distress, work satisfaction and intent to leave their organisation and the profession. Background The emergence of COVID‐19 has significantly impacted the psychological and mental well‐being of frontline healthcare workers, including nurses. To date, no studies have been conducted examining how this fear of COVID‐19 contributes to health, well‐being and work outcomes in frontline nurses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
675
8
43

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 657 publications
(775 citation statements)
references
References 36 publications
49
675
8
43
Order By: Relevance
“…Research has indicated that due to the ongoing COVID-19 pandemic, people are experiencing high levels of stress, depression, and anxiety, as well as levels of post-traumatic stress that are above the cut-off for post-traumatic stress disorder (PTSD) [5][6][7]. Healthcare professionals who come in close contact with COVID-19 patients are deeply affected by this novel virus and experience mental health challenges, including stress, depression, anxiety, PTSD, and burnout [8][9][10][11][12][13], which can have deleterious effects on their quality of life [11] and increase their turnover intention [14]. In addition, their concentration, comprehension, and decision-making ability can be affected by these psychological difficulties, which could, in turn, affect infectious disease management [15].…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that due to the ongoing COVID-19 pandemic, people are experiencing high levels of stress, depression, and anxiety, as well as levels of post-traumatic stress that are above the cut-off for post-traumatic stress disorder (PTSD) [5][6][7]. Healthcare professionals who come in close contact with COVID-19 patients are deeply affected by this novel virus and experience mental health challenges, including stress, depression, anxiety, PTSD, and burnout [8][9][10][11][12][13], which can have deleterious effects on their quality of life [11] and increase their turnover intention [14]. In addition, their concentration, comprehension, and decision-making ability can be affected by these psychological difficulties, which could, in turn, affect infectious disease management [15].…”
Section: Introductionmentioning
confidence: 99%
“…Emerge neste período o desconhecimento de uma nova doença, a preocupação de contraí-la e transmitir à família (2,7,12) . Sinais de alerta como ansiedade, angústia e medo descritos pelos participantes são frequentes perante situações de potencial perigo, originando potencial perturbação no bem-estar do enfermeiro, mas, permitindo lidar com as novas situações (13)(14)(15)(16)(17) . Também o estresse, realidade do exercício profissional, neste período, assumiu maior intensidade.…”
Section: Discussionunclassified
“…Ambiente e organização do trabalho são fundamentais para a qualidade de vida no trabalho e a segurança dos pacientes, sendo que os processos de mudança determinam o fomento de recursos individuais e organizacionais para um processo adaptativo (17) . As rápidas alterações organizacionais, a mobilidade de enfermeiros para serviços COVID-19, a alteração dos turnos de trabalho e a indisponibilidade para pausas devido ao uso dos equipamentos de proteção individual já descritos na literatura foram também identificados no discurso dos participantes.…”
Section: Discussionunclassified
See 2 more Smart Citations